Executive Committee Minutes 2020-05-07 - Academic Senate:::::::::
Agenda – item added: BA degrees in Spanish and French – Approved. Minutes of 4/23/2020 – Approved. Chair Report. President Report. Provost Report. Vice President of Administration and Finance Report. Vice President for Student Affairs Report. Associated Students Report. Course Materials Cost Report – referred to first meeting of Ex Com in the fall. From EPC: Dance elevation to Major, Revision to Education Leadership Administrative Service Credential and Revision to BAs in French and Spanish all approved for the Senate's consent calendar. From S&F: ExCom Transition Date Recommendations and Summer Ex Com quorum decision – Approved. EPC report. FSAC report. SAC report. Senate agenda approved.